Water‐rich bending faults at the Middle America Trench. (16th August 2015) - Naif, Samer; Key, Kerry; Constable, Steven; Evans, Rob L.
Abstract: The portion of the Central American margin that encompasses Nicaragua is considered to represent an end‐member system where multiple lines of evidence point to a substantial flux of subducted fluids. The seafloor spreading fabric of the incoming Cocos plate is oriented parallel to the trench such that flexural bending at the outer rise optimally reactivates a dense network of normal faults that extend several kilometers into the upper mantle. Bending faults are thought to provide fluid pathways that lead to serpentinization of the upper mantle. While geophysical anomalies detected beneath the outer rise have been interpreted as broad crustal and upper mantle hydration, no observational evidence exists to confirm that bending faults behave as fluid pathways. Here we use seafloor electromagnetic data collected across the Middle America Trench (MAT) offshore of Nicaragua to create a comprehensive electrical resistivity image that illuminates the infiltration of seawater along bending faults. We quantify porosity from the resistivity with Archie's law and find that our estimates for the abyssal plain oceanic crust are in good agreement with independent observations. As the Cocos crust traverses the outer rise, the porosity of the dikes and gabbros progressively increase from 2.7% and 0.7% to 4.8% and 1.7%, peaking within 20 km of the trench axis. We conclude that the intrusive crust subducts twice as much pore water as previously thought, significantly raising the flux of fluid to the seismogenic zone and the mantle wedge. Key Points: Fluids penetrate the crust at the outer rise Bending faults double porosity of the lower crust Significantly more pore water is subducted than previously thought